Entropically Favoured Assembly of Pyrazine‐Based Helical Fibers into Superstructures: Achiral/ Chiral Guest‐Induced Chirality Transformation. Issue 45 (25th September 2019) - Sharma, Sonia; Kataria, Meenal; Kumar, Manoj; Bhalla, Vandana
Abstract: The development of synthetic helical structures undergoing stimuli‐responsive chirality transformations is important for an understanding of the role of chirality in natural systems. However, controlling supramolecular chirality in entropically driven assemblies in aqueous media is challenging. To develop stimuli‐responsive assemblies, we designed and synthesized pyrazine derivatives with l ‐alanine groups as chiral building blocks. These systems undergo self‐assembly in aqueous media to generate helical fibers and the embedded alanine groups transfer their chirality to the assembled structures. Furthermore, these helical fibers undergo a Ni 2+ ‐induced chirality transformation. The study demonstrates the role of intermolecular hydrogen bonding, π–π stacking, and the hydrophobic effect in the Ni 2+ ‐mediated transition of helical fibers to supercoiled helical ensembles which mimic the formation of superstructures in biopolymers. Abstract : Twist and shout : A pyrazine derivative undergoes a helical transformation in aqueous media with l ‐alanine as a chiral handle. The generation of helical fibers in aqueous media, the helical‐to‐coiled‐superhelix transition in the presence of achiral guests (Ni 2+ ions), and the transition of the supercoiled helix to a superhelix in the presence of chiral guests (d /l ‐histidine) are entropically driven processes.